An Approximate Analytical Method of the Nonlinear Vibroacoustic Coupling System - Qizheng Zhou; Deshi Wang; Yongyong Zhu (Shock and Vibration)
An approximate analytical method of the nonlinear vibroacoustic coupling system is proposed for the first time. Taking the Duffing oscillator-plate-medium system as an example, the nonlinear vibroacoustic coupling equations are developed using variational principle. The two major difficulties which lie in solving the coupling equations are the uncertain motion of the oscillator and the surface acoustic pressure on the plate, a system for which the fluid-structure coupling cannot be neglected. Based on the incremental harmonic balance (IHB) method, the motion of the oscillator is expressed in the form of the Fourier series, and then the modal expression method and the incoherent assumption are employed to discretize the displacement and the surface pressure of the plate. Then the approximate analytical solution is given by the IHB method. The characteristics of acoustic radiation and surface quadratic velocity of the plate, the nonlinear characteristics of oscillator, and the influence of the excitation frequency and the nonlinear stiffness on the results are investigated by the numerical simulation. The results show that the excitation at the frequency close to the natural frequency of the oscillator can produce a significant response of the third-harmonic generation which determines the vibroacoustic characteristics of the plate.